Becoming a teacher with a disability: a systematic review - Rosa Bellacicco; Heidrun Demo (Firenze University Press, 2019)
The number of students with disabilities in higher education has increased along with growing literature which has explored their experience in university. However, little research exists on the unique issues and challenges posed by the courses that lead to a professional qualification, such as nursing and teacher training. Specifically, the purpose of this systematic review is to investigate the inclusion of students with disabilities in teacher training. Twenty-two primary studies, published between 1990 and 2018, have been included in the review. Five main thematic areas - a result of the synthesis of the available evidence - are discussed here. Suggestions for future research are also provided.   Diventare un insegnante con disabilità: una revisione sistematica. Il numero di studenti con disabilità nelle università è aumentato e, allo stesso tempo, una letteratura crescente ha esplorato le loro esperienze accademiche. Tuttavia, esistono poche ricerche sulle questioni e sfide uniche poste dai corsi abilitanti alla professione, come infermieristica e la formazione insegnanti. Nello specifico, lo scopo di questa revisione sistematica è indagare il tema dell'inclusione degli studenti con disabilità nella formazione insegnanti. Ventidue studi primari, pubblicati tra il 1990 e il 2018, sono stati inclusi nella revisione. Cinque principali aree tematiche - esito della sintesi delle evidenze disponibili - vengono discusse. Sono inoltre forniti suggerimenti per ricerche future.